Immunohistological Localization of the MrkD Adhesin in the Type 3 Fimbriae of Klebsiella pneumoniae - Tarkkanen, Ann-Mari (American Society for Microbiology, 1998)
The adhesive minor protein MrkD of the type 3 fimbria of Klebsiella pneumoniae was expressed and purified from Escherichia coli as a fusion protein with an N-terminal polyhistidine tail. Polyclonal antibodies raised against MrkD specifically recognized the MrkD peptide in Western blots of fimbrial preparations. Immunoelectron microscopic analyses showed that the anti-MrkD immunoglobulins bound to the tip of the plasmid-encoded variant of the type 3 fimbria of K. pneumoniae, whereas no binding to the chromosomally encoded MrkD-deficient type 3 fimbrial variant of K. pneumoniae was detected. Immunoglobulins from an antiserum raised against purified type 3 fimbrial filaments bound laterally to both type 3 fimbrial variants. The anti-MrkD antibodies also bound to the tip of a papG deletion derivative of the E. coli P fimbria complemented with mrkD, indicating that MrkD structurally complements a PapG mutation in the P fimbria of E. coli.